Fall of eagles [videorecording (DVD)] - Stewart, Patrick, 1940-; Kitchen, Michael, 1948-; Rhys-Davies, John; Whitemore, Hugh; Hays, Bill (KOCH Vision, 2006)
Dramatization of the fall of the three great ruling houses of Europe in the latter half of the 19th and early part of the 20th centuries, the Hapzburgs of Austria-Hungary, the Romanovs of Russia, and the Hohenzollerns of Germany.